Building Entrepreneurial Capacity Among Women Through Accounting Training - Lelengboto, Abraham; Wardoyo, Sharon Kumaratih Dewi; Lompoliu, Erienika Meiling; Moniung, Rini Veronica (Universitas Klabat, 2025)
In alignment with Indonesia’s people-centered economic framework under the 1945 Constitution, micro, small, and medium enterprises (MSMEs) contribute over sixty percent to the national gross domestic product. A significant share of this contribution is supported by women entrepreneurs, although they continue to face barriers in accessing entrepreneurial literacy, particularly in financial management. To address this issue, the Office of Cooperatives and MSMEs, in collaboration with Klabat University, implemented a community engagement program providing basic bookkeeping training for women entrepreneurs in Bitung City, North Sulawesi. The training design was informed by value chain theory, which identifies financial record-keeping as a vital supporting activity in value creation. A participatory learning approach was adopted, encouraging active discussion and culminating in an accounting practicum. Program effectiveness was assessed through pre- and post-training surveys, with data analyzed using descriptive and inferential statistics. A mean-difference test was applied to measure changes in participants’ competencies. The results show a significant increase in accounting knowledge following the intervention, indicating that the participants benefited from the training and demonstrated strong commitment to enhancing their entrepreneurial capacities. Keywords— People-centered economy, Women, Entrepreneurship, Accounting, MSMEs